The 20 points and Anti-Federal sentiment in Sabah politics: a never-ending conflict? - Jeniwaty Mohd Jody,; Mohammad Agus Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Upon joining the Federation of Malaysia in 1963, Sabah was promised privileges in exchange for protecting the state’s interests and rights spelt out in the 20 Points. However, after 60 years in the Federation of Malaysia, Sabah was frequently unsatisfied due to the federal government’s failure to meet the agreement. As a result, an anti-federal sentiment in Sabah emerged, urging the state to quit the Federation of Malaysia. With the use of federalism as an analytical tool, together with primary and secondary sources such as interviews, books, journals and newspapers being research data, this article discusses the issues that persist in the 20 Points. This article contended that the federal government has failed to address five major issues, namely (i) the payment of oil royalties, (ii) the financial allocation and development gap, (iii) the immigration and foreigner issues, (iv) Sabah’s constitutional status and (v) Borneonisation, which have resulted in anti-federal sentiment in Sabah. The federal government’s failure to address the issues created a substantial economic imbalance between Sabah and other states, an influx of illegal immigrants and the Peninsular Malaysians dominating government offices.